2021
DOI: 10.47405/mjssh.v6i3.690
|View full text |Cite
|
Sign up to set email alerts
|

Kebimbangan dan Efikasi Kendiri Terhadap Pembelajaran Matematik dalam kalangan Pelajar Tingkatan Empat

Abstract: Pembelajaran matematik masa kini tidak lagi hanya menekankan pembinaan tingkah laku pelajar yang dapat dikesan daripada tindak balas dan rangsangan. Bahkan juga memberi penekanan bagi melihat bahawa pendidikan matematik disifatkan sebagai subjek yang sukar di samping melibatkan interaksi dinamik antara sifat dalaman pelajar, faktor fizikal dan faktor persekitaran sosiobudaya. Persaingan sengit dan perubahan teknologi yang pesat memerlukan kepintaran matematik dan wajib diambil hampir dalam kesemua latar belaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…Mathematical anxiety is a common phenomenon among secondary school students (Zay & Kurniasih, 2023). Several studies, both within and outside the country, have found that secondary school students experience high levels of mathematical anxiety (Bornaa, Rahaman, & Iddrisu, 2023;Estonanto & Dio, 2019;Hui & Rosli, 2021;Mutegi et al, 2021;Suren & Kandemir, 2020;Taley & Ndamenenu, 2022). High levels of anxiety refer to the fear and difficulty in participating in activities related to mathematics (Muner & Rosli, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematical anxiety is a common phenomenon among secondary school students (Zay & Kurniasih, 2023). Several studies, both within and outside the country, have found that secondary school students experience high levels of mathematical anxiety (Bornaa, Rahaman, & Iddrisu, 2023;Estonanto & Dio, 2019;Hui & Rosli, 2021;Mutegi et al, 2021;Suren & Kandemir, 2020;Taley & Ndamenenu, 2022). High levels of anxiety refer to the fear and difficulty in participating in activities related to mathematics (Muner & Rosli, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students experiencing it may feel anxious and less enthusiastic when performing numerical calculations or solving math problems (Hunt & Zakaria, 2018;Prodromou & Frederiksen, 2018). Muner and Rosli (2023) found that mathematical anxiety has a negative impact on students' math achievements and can hinder them from achieving their educational goals. Therefore, it is crucial for teachers and researchers to understand the factors influencing mathematical anxiety and how to help students overcome this issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) who stated that kinesthetic students find it difficult to make mathematical connections well because they learn by manipulating objects or applying them to everyday life. Briefly, since mathematics learning is more abstract (Hui and Rosli, 2021), it is difficult for these students to relate the mathematical concepts learned to their real life. Furthermore, the teaching method of Mathematics teachers, which is entirely contingent on explanations in class without diversifying the teaching methods, limits kinesthetic students' understanding of abstract mathematical concepts.…”
Section: Academic Procrastinationmentioning
confidence: 99%
“…This causes students to experience difficulties in solving questions or other mathematical problem-solving exercises even if they involve the same question form (Yuanita et al, 2018). Students also think that mathematics assignments are too complicated and difficult because mathematics learning is more abstract (Hui and Rosli, 2021). Therefore, practicing the right learning style can create a positive atmosphere when learning mathematics (Mundia and Metussin, 2019) and subsequently reduce the tendency of students to practice academic procrastination in the subject of Mathematics.…”
Section: Introductionmentioning
confidence: 99%